Penanggulangan Tindak Pidana Pencurian Satwa Lindung - Samaludin Samaludin (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2021)
The purpose of this study was to determine law enforcement against the thefl of protected animals. The legal research method used in this paper is an empirical legal research method. The data used are primary and secondary data. Then, the juridical qualitative data analysis was carried out. Based on the results of the research, it shows that the factors causing the crime of theft of protected animals are economic, educational, environmental, and law enforcement, further law enforcement and prevention of criminal acts of theft of protected anilmals are carried out by stricter law enforcement in order to have a clear effect as perpetrators of criminal acts and countermeasures are carried out through preventive and repressive measures.